The effect of Gandarusa Leaf extract (Justicia gendarussa Burm F.) Administration on Estradiol Hormone Level and the Amount of Antral Ovarium Follicle on Female Mice - Laili, Ni'mah Hidayatul; Nasihun, Taufiqurrachman; Sumarawati, Titiek (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2018)
Background: Physiologically, woman experiencing aging characterized by menopause. Gandar usa leaf contains isof lavon, a phytoesterogen expected to be used as esterogen replacement therapy.Objective: the aim of this research is to investigate the administrative ef fect of gandar usa leaf extract on the increase of estradiol hor mone level and the number of antral ovarium follicle of female mice.Methods: This is experimental study with posttest only control group research design. Samples are 24 balb-c female mice, aged 16-17 months, weighed 19-35 grams, divided into 4 groups. Control group (Ctrl-G) were given 0.48 ml aquadest; group JB10-G, JB20-G, and JB30-G, each were given gandar usa leaf extract with concentration 10%, 20%, dan 30% in volume 0.48 ml orally twice a day. Af ter treatment, dissection were conducted to make ovarium histology preparation with Hematoxylin Ehrlich-Eosin staining, obser vation were conducted using microscope.Results: Post hoc analysis indicated that the estradiol level and the number of antral ovarium follicle on administration of gandar usa leaf extract with concentration 10%, 20%, dan 30% are signif icantly higher, p < 0.05. The increase of estradiol level with extract concentration of 10% are signif icantly negatively cor related with the number of antral ovarium follicles p<0.05. negatively cor related with the number of antral ovarium follicles p<0.05.Conclusion: The administration of gandar usa leaf extract increase the estradiol hor mone level and the number of antral ovarium follicle in female mice.